Behaviour of reinforced recycled concrete aggregate beam with addition of steel fiber and kenaf fiber (hybrid) - Muhammad Norqayyuum, Md Nasib (2017)
The use of recycled concrete aggregate (RCA) in concrete mixture as partial replacements of natural coarse aggregate is growing interest in the construction industry. Concrete recycling gains importance because it protects natural resources. However, generally contains amount of recycle concrete aggregates in concrete. This tends to increase the drying shrinkage properties of the new concrete and it will leading to problems with unworkable mix and strength. The idea to add fibers to a concrete mixture containing recycled aggregate may change material properties concrete and it will improve behaviour. This study aim to investigate the strength of reinforced concrete beam by replacing 25% of natural aggregate with the recycle aggregate and To study the structural behaviour of steel fiber and kenaf fiber (hybrid), when added it into the recycle reinforced concrete beam. In this study, four numbers of beam constructed, which is normal control beam and another beam with 25 % of recycle concrete aggregates added with (0%,1% and 2%) of steel fiber and kenaf fiber (hybrid). By adding steel fiber and kenaf fiber (hybrid) into the recycled concrete beam should be enhance the concrete strength, control concrete cracks and weak bonds of concrete.